THE ROLE OF VILLAGE FUND CASH TRANSFER AS AN EFFORT REDUCING POVERTY RATES IN MEKARSARI VILLAGE, CIANJUR DISTRICT, CIANJUR REGENCY - Muhamad Fariz Salman Zulkipli; Soni Akhmad Nulhaqim; Gigin Ginanjar Kamil Basar (Jurnal Ekonomi, 2023)
The Covid-19 pandemic not only disrupts health but also has an impact on the economic order of all countries. Launching from the Benefita 5(2) Journal, the impact of the pandemic on the economy can cause low investor sentiment toward the market which ultimately makes the market negative. The Covid-19 pandemic entered Indonesia in 2020, the impact felt made the Indonesian economy bad, especially for people in the poor category, so there needs to be government efforts to overcome this problem. And to overcome this, one of the efforts made by the Indonesian government is to refocus the budget from various existing budget items. And one of the budget items that is also being refocused is the Village Fund. The main priority for using Village Funds this year is a social protection program in the form of Village BLT. Village BLT is a cash gift to poor or indigent families in the village sourced from the Village Fund. This provision aims to help the rural poor, reduce the economic impact of the Covid-19 pandemic, and become an additional income to increase the purchasing power of the poor in meeting their basic daily needs. Village funds, which are intended for village development and development, are diverted into cash assistance funds called Village Fund Direct Cash Assistance (BLT Dana Desa). Therefore, this study aims to determine the role of Village Fund BLT in reducing the poverty level of people in the village. To achieve the above goals, researchers here use a descriptive qualitative research approach. The method of data collection is structured interviews and documentation. Data analysis used consists of data education, information collection, and conclusions. The results showed that the Village Fund Direct Cash Transfer greatly helped the community's economy. Because it increases people's purchasing power.